Building resilience of Mongolian rangelands: a trans-disciplinary research conference - Fernandez-Gimenez, Maria E., author; Baival, Batkhishig, author; Fassnacht, Steven R., author; Wilson, David, author; Ganbold, Chimgee, author; Vanluu, Dugermaa, author; Purevsuren, Munkhzul, author; Nutag Action and Research Institute, publisher (Colorado State University. Libraries, 2015)
Mongolia is a semi-arid and arid country in Asia where the climate has been changing more drastically than many other locations across the globe. The proceedings of the "Trans-disciplinary Research Conference: Building Resilience of Mongolian Rangelands" is divided into five sections: 1) Rangeland Ecology and Management, 2) Climate Change and Hydrology, 3) Institutional Innovations in Mongolian Rangelands, 4) Social and Economic Development in Rural Mongolia, and 5) Methods of Knowledge and Data Integration. The papers presented provide cause for concern regarding observed changes in climate, rangeland conditions and livestock populations, as well as reasons for hope and motivations for action to address the current challenges. We hope that this volume and the conference it accompanies, will inspire renewed commitment to support science and science-based policy-making and management to sustain Mongolia's unique natural and cultural heritage as they adapt to a changing planet.
The Building resilience of Mongolian rangelands: a trans-disciplinary research conference was held on June 9-10, 2015 in Ulaanbaatar, Mongolia.
Edited by: María E. Férnández-Giménez, Batkhishig Baival, Steven R. Fassnacht, David Wilson. Translated by: Chimgee Ganbold, Dugermaa Vanluu, Munkhzul Purevsuren.